2021
DOI: 10.3126/dristikon.v11i1.39141
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Challenges Faced by Secondary Teachers while Integrating ICT in Nepalese ESL Classrooms

Abstract: Teaching and learning in the 21st century has been embedded with technology. Use of Information and Communication Technology (ICT) plays a crucial role in ameliorating knowledge acquisition in general and enhancing English Language mastering in particular. The government of Nepal has made provision of integrating ICTs in school education to enhance quality education and make both teachers and learners confident and competitive in the present global world. The teachers are the real implementers of the policy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…A study in Nepal by Rana and Rana (2020) revealed that teachers were experiencing various challenges such as proper trainings and ICT infrastructures to integrate ICT in classroom They also reported that teachers had strong will power to develop their ICT skills to imply in their teaching and learning activities. In a similar study, Khadka (2021) concluded that despite sufficient skills and knowledge to use ICT tools and application, teachers' high motivation guided them to gradual shift for integration of ICT in English language teaching. Moreover, a study by Rana et al (2018) reported that the incorporation of inclusive digital tools into teaching and learning activities has partially transformed the role of teachers in the classroom, fostering a conducive learning environment and improving the overall classroom dynamics.…”
Section: Capacitating Teachers In Ictmentioning
confidence: 99%
“…A study in Nepal by Rana and Rana (2020) revealed that teachers were experiencing various challenges such as proper trainings and ICT infrastructures to integrate ICT in classroom They also reported that teachers had strong will power to develop their ICT skills to imply in their teaching and learning activities. In a similar study, Khadka (2021) concluded that despite sufficient skills and knowledge to use ICT tools and application, teachers' high motivation guided them to gradual shift for integration of ICT in English language teaching. Moreover, a study by Rana et al (2018) reported that the incorporation of inclusive digital tools into teaching and learning activities has partially transformed the role of teachers in the classroom, fostering a conducive learning environment and improving the overall classroom dynamics.…”
Section: Capacitating Teachers In Ictmentioning
confidence: 99%
“…benefits in helping to provide access to learning for everyone, thereby removing physical barriers as a factor for learning in the classroom (Pei & Wu, 2019), even it is seen as something that is effective to implement However, according to (Pilkington, 2018) it is undeniable that not all learning can be transferred to an online learning environment. The obstacles faced in online learning are the lack of adequate supporting facilities and infrastructure (Khuluqo et al, 2021); (Suherman, 2021); (Karalis, 2020), lack of mastery of technology skills by teachers (Khadka, 2021); (Maphalala et al, 2021); (Pandey et al, 2021), limited internet network (Simamora, 2020); (Bariham et al, 2021). One of the subjects affected by the Covid-19 pandemic is Physical Education, Sports, and Health.…”
mentioning
confidence: 99%